2011
DOI: 10.1038/nmat2951
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement in organic solar cells with ferroelectric polymers

Abstract: Polymeric organic photovoltaic (OPV) cells with polymer-fullerene bulk heterojunction are promising candidates for future low-cost, high-performance energy sources, owing to their low material and processing costs and mechanical flexibility. 1,2 High efficiencies of 6-8% have been realized in polymeric OPVs by reducing both the optical bandgap and the highest occupied molecular orbital of the semiconducting polymers, and by optimizing the morphology of polymerfullerene blend film with thermal annealing and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
439
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(458 citation statements)
references
References 48 publications
11
439
0
Order By: Relevance
“…Considering that the SLs with free carriers inside can act as electrodes for poling, only the dimension of such SLs determines the V c ( ¼ E c d f ). The f in dc devices with small dimensional ferroelectric components, such as the OPV devices in previous reports 14,15 , may be sufficient for poling. As shown in Supplementary Note 1 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Considering that the SLs with free carriers inside can act as electrodes for poling, only the dimension of such SLs determines the V c ( ¼ E c d f ). The f in dc devices with small dimensional ferroelectric components, such as the OPV devices in previous reports 14,15 , may be sufficient for poling. As shown in Supplementary Note 1 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is difficult to determine the contribution from the oriented E s , since random distributed local fields and field amplification due to its linear dielectric property may also help for photocurrent generation. Considering an even smaller dimension of the ferroelectric components and a larger f with two injecting contacts (the resultant bipolar injection can induce plenty of free carriers for poling) of the OPV devices in the previous reports 14,15 , the ferroelectric polarization may have already occurred, and the resultant oriented E s may play a partial role for the performance enhancements in their devices. Since the large amount of free charges due to the dc photocurrent, which may induce good compensation for polarization, there should not be a large E s across the whole devices, as proposed in Yuan et al 15 In summary, the double-wave method and photocurrent transients have been employed to probe net fields in organic materials from poled P(VDF-TrFE) films.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, NWs‐based PV will have great application in flexible power source compared to bulk materials. However, a large source of loss in this type of device is nonradiative recombination of the photogenerated carriers 8. Therefore, new strategies are necessary to reduce this recombination and significantly increase device efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A prime example of the latter is tandem solar cells. 4 In a recent article, Yuan et al 5 reported on the efficiency enhancement in organic solar cells by incorporating a ferroelectric polymer interlayer between the electrodes and the photoactive layer. The enhanced efficiency was explained by the presence of an electric field due to the polarization of the ferroelectric layer, leading to enhanced exciton dissociation and, therefore, increased power conversion efficiency from 1%-2% to 4%-5%.…”
mentioning
confidence: 99%